Likovno-intelektualni razvoj učencev v različnih programih osnovnošolskega izobraževanja - Duh, Matjaž; Herzog, Jerneja; Lazar, Melita (Revija za elementarno izobraževanje, 2014)
Artistic and Intellectual Development of Children in Different Basic School Education Programmes. The article presents the results of a study that investigated the level of artistic and intellectual development of students in different primary school education programmes. The differences were monitored in the groups of sixth-grade students of regular basic schools and of students of basic schools with an adapted programme and a lower educational standard in the regions of Štajerska and Prekmurje. The study also examined any gender-related differences. The study results indicate that there are differences in the artistic and intellectual development of children between the group of children with normal development and the group of children with special needs in favour of the group of children with normal development. No statistically significant gender-related differences were established in the level of artistic and intellectual development.